Analisis Yuridis Proses Peninjauan Kembali Dalam Sengketa Pajak Penghasilan Pasal 23 (Studi Kasus Putusan Nomor 6555/B/Pk/Pjk/2023) - Yosheko Casimira Morgan (Mahalini: Journal of Business Law, 2025)
This study aims to understand the legal aspects governing judicial review (Peninjauan Kembali or PK) in income tax disputes under Article 23, as regulated in Law Number 14 of 2002 on Tax Courts and Law Number 50 of 2022 on Procedures for Exercising Rights and Fulfilling Tax Obligations. The research method used is normative juridical, with an approach that examines and interprets the legal rules relevant to the research topic. The findings indicate that the judicial review (PK) filed by PT Sharp Electronics Indonesia met the formal requirements as stipulated in the General Provisions and Tax Procedures Law and the Tax Court Law. The petitioner presented valid arguments and evidence; however, the Supreme Court ruled that no significant new evidence was found, and there were no errors in the application of the law by the Tax Court. The Supreme Court's decision emphasizes the importance of accurate and consistent application of the law to support legal certainty in tax disputes.